(untitled) (Boston, 2007)
Appropriate for the non-major/allied health student, this authoritative text carefully explains the fundamentals of microbiology, providing a general overview of the principles followed by more detailed explanations. With its clear and concise writing style, "Microbiology: A Human Perspective" offers modern coverage on such topics as genomics, biofilms, and quorum sensing. A body systems approach is used in the coverage of diseases.
Keywords: Microbiology,Microbiology,Communicable diseases; Methods,Microbiology